Influence of Rainfall Over Eastern Arabian Sea on Its Salinity. Issue 7 (19th July 2019) - Behara, Ambica; Vinayachandran, P. N.; Shankar, D.
Abstract: The west coast of India and the adjoining eastern Arabian Sea (EAS) is one of the high rainfall zones of Indian summer monsoon. The summer monsoon rainfall in this region is about 1, 036 km 3, which is comparable to the annual runoff of the Ganga‐Brahmaputra river system. We have investigated the impact of EAS rainfall and Bay of Bengal (BoB) low‐salinity water on the Arabian Sea salinity with a suite of experiments using an ocean general circulation model. The sea surface salinity (SSS) of EAS decreases progressively from June to September by 0.5 to 1 psu. A numerical experiment that isolates the effect of EAS rainfall suggests that this SSS decrease is largely due to local rainfall over the EAS. The spatial pattern of SSS decrease, however, is influenced by the prevailing West India Coastal Current. The role of low‐salinity water originating in the BoB on reducing the EAS salinity has also been examined. In the South Eastern Arabian Sea, during winter, the SSS decreases by about 1.5 psu. This freshening is caused by rainfall during the early winter in the southwestern BoB between 6°N and 15°N. Neither rainfall to the north of 15°N nor river runoff into the BoB contributes much to the South Eastern Arabian Sea freshening during winter. Key Points: The Western Ghats and the eastern Arabian Sea receive large amount of rainfall during summer monsoon The rainfall over eastern Arabian Sea decreases its salinity by 0.5–1 psu The low‐salinity water arriving at the eastern Arabian Sea during winter originates from the southern Bay of Bengal rainfall